Pengembangan Media Video Pembelajaran Matematika Berbentuk Animasi Menggunakan Canva - Jimmy; Yulianai, Refi Elfira; Kusumawati, Nyimas Inda (Program Studi Pendidikan Matematika, Universitas Islam Negeri Raden Fatah Palembang, 2024)
This research aims to produce a mathematics learning video and determine its validity and practicality. In this research, the researcher used Canva to create animated mathematics learning videos with the material of flat-sided cube and rectangular prism. The development uses the ADDIE model which consists of: analysis, design, development, implementation, and evaluation. The research subjects were 28 eighth-grade students in the second semester of the 2023-2024 academic year. The data collection methods used were tests and questionnaires, accompanied by documentation. The results of this study are that the produced media is feasible, useful, and has the potential to be influential. The evaluation results from the media experts stated that the video material is very good, with a percentage score of 81.25%; material experts stated that the video material is good, with a percentage score of 95.83% in the very good category; language experts stated that the video material is sufficient, with a percentage score of 89.28% in the very suitable category. In addition to the evaluation of student questionnaire responses, 88.24% of respondents at that time stated